Formação do auxiliar de enfermagem: um estudo a partir da produção científica brasileira (1990-2008) - Cabral, Vera Lucia Moreira (2010)
The present study aims to look at the state of the art or of the knowledge achieved in Brazilian scientific production, through the analysis of dissertations and theses, registered in the Capes Theses Database, regarding the nursing assistant and focusing on the issue of vocational training. This study is both analytic-descriptive and exploratory in character. Nineteen theses were selected from among the 527 dissertation and theses summaries found dealing with nursing assistants’ vocational education, whether directly or indirectly. The research shows that while there is low appeal among researchers to study the theme, the existing scientific production demonstrates a significant concern with both the curricular and pedagogical aspects, as well as with the pedagogical practice of the teacher/trainer. The “Larga Escala” Project, undertaken at national level, and the “Xamã” Project, which took place in 26 indigenous communities, were the two main projects researched regarding the training and the vocational education of the nursing assistant. The study reinforces national trends regarding Brazilian scientific production: the largest concentration of research projects in the southeast region of the country, the scientific leadership of the Sao Paulo University (USP), and the indisputable concentration of scientific research in state-owned universities. The research also reveals the field of education as a field of knowledge that gains foreground in terms of researchers´ interests, in particular for their qualification at masters´ level, outreached only by nursing.